#### Answer

$-x^2-5x+5$

#### Work Step by Step

$(x^2-2x+1)-(2x^2+3x-4)=(x^2-2x^2)+(-2x-3x)+(1+4)=-x^2-5x+5$

Chegg costs money, GradeSaver solutions are free!

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$-x^2-5x+5$

$(x^2-2x+1)-(2x^2+3x-4)=(x^2-2x^2)+(-2x-3x)+(1+4)=-x^2-5x+5$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.